2009
DOI: 10.1037/a0014251
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of head and body movement with motion of the audible environment.

Abstract: The authors asked whether standing posture could be controlled relative to audible oscillation of the environment. Blindfolded sighted adults were exposed to acoustic flow in a moving room, and were asked to move so as to maintain a constant distance between their head and the room. Acoustic flow had direct (source) and indirect (reflected) components. Participants exhibited strong coupling of postural motion with room motion, even when direct information about room motion was masked and was available only in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
3
20
1
Order By: Relevance
“…These observations are in line with research showing the robustness of the sway-target coupling in postural tracking regardless of whether the target is visually or acoustically presented [8]. In our study though, coupling of sway to the pacing stimulus was stronger than that to the visual target.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These observations are in line with research showing the robustness of the sway-target coupling in postural tracking regardless of whether the target is visually or acoustically presented [8]. In our study though, coupling of sway to the pacing stimulus was stronger than that to the visual target.…”
Section: Discussionsupporting
confidence: 94%
“…One raising concern is the durability and generalization of practice effects. Standing while tracking the for-aft motion of a visually [7] or audibly [8] presented moving target produced robust sway-target and ankle-hip relationships suggesting strong perception-action coupling in both sensory-motor workspaces. Yet, learning of a new visually driven ankle-hip relationship presented by a complex Lissajous figure did not generalize across different types of tasks involving similar coordination patterns [9].…”
Section: Introductionmentioning
confidence: 97%
“…Sound reflections are also useful when estimating the size and the shape of a room (Picinali et al, 2014). Stoffregen et al (2009) even showed that blindfolded subjects were able to detect the movement of a room surrounding them solely from the reflected components of a sound field emitted inside the room, and to correlate their head movements with room motion.…”
Section: Experiments 1: Building An Auditory Environmentmentioning
confidence: 99%
“…Human behavior is constantly shaped by the properties, constraints, and affordances of the environment ( Gibson, 1986 ), including the movements of environmental objects and other individuals (e.g., Chartrand and Bargh, 1999 ; Buekers et al, 2000 ; Lopresti-Goodman et al, 2008 ; Richardson et al, 2010 ). Accordingly, the limb and body movements of actors often become naturally synchronized and coordinated with periodic occurrences in the environment when they are coupled to them via visual (e.g., Dijkstra et al, 1994a , b ; Buekers et al, 2000 ), auditory (e.g., Repp and Penel, 2004 ; Repp, 2006 ; Stoffregen et al, 2009 ), or haptic (e.g., Jeka et al, 1998 ) information. Evidence indicates that these abilities to engage in multimodal entrainment to environmental rhythms ( Phillips-Silver and Trainor, 2005 ) and to detect cross-modal rhythmic asynchronies ( Hannon, 2008 ) are present early in infancy, revealing a propensity for attunement of human perception and action to such external events.…”
Section: Introductionmentioning
confidence: 99%